ANALISIS KESESUAIAN KAWASAN HUTAN LINDUNG DALAM RANGKA ARAHAN PENATAAN RUANGDI KABUPATEN KONAWE UTARAPROVINSI SULAWESI TENGGARA - Muhamad Yusuf Baso; Sitti Marwah; Lukman Yunus (Jurnal Perencanaan Wilayah, 2020)
ABSTRACT This study aims (1) to determine protected forest areas based on scoring analysis in North Konawe District, (2) to determine the direction of protection forest designation in North Konawe District, (3) evaluate the suitability of protected forest areas that have been determined through a Minister of Forestry Decree and Environment with the condition of the direction of forest area in North Konawe Regency, and (4) evaluating the suitability of protected forest areas stipulated in the North Konawe Regency spatial planning document (RTRW) with maps of forest area development. The method or technique of sampling is determined intentionally (purposive sampling), based on field conditions through a Ground Check Ground study to determine field conditions. The sample in this study consisted of forest area managers, community groups, and protected forest areas located in Asera District and LasoloKepulauan District. This research uses descriptive analysis and map overlay analysis. The results showed that (1) The entire administrative area of North Konawe Regency, the area classified as protected forest area based on the scoring criteria was 152,627.00 Ha or 34.52% of the area of North Konawe Regency; (2) The direction of the protected forest area in North Konawe Regency is 147,996.36 Ha which includes Langgikima, Molawe, Oheo, Wiwirano, Motui, Sawa, Lembo, Lasolo, Andowia, Lasolo Islands, and Asera Districts; (3) The suitability of protected forest areas that have been determined through the Decree of the Minister of Forestry and the Environment with the condition of the direction of the forest area in North Konawe Regency is that there is a protected forest area (based on a map of the direction of the forest area) allocated (in the map of forest area development) into a cultivation area (HP) covering an area of 3,493.46 Ha, there are Other Use Areas (APL) in protected forest maps of forest area development covering 10.31 Ha, and there are protected forest areas (in forest area development maps) allocated (based on forest area landing maps) become a cultivation area (HPT) covering an area of 8,051.78 hectares spread throughout the sub-district, so that a limited production forest area of 8,051.78 hectares; and (4) Based on the suitability of the protected forest area stipulated in the North Konawe Regency Spatial Plan (RTRW) with a map of the forest area development there is a difference in the area of the forest area because the North Konawe Regency spatial pattern still uses SK. 465 / Menhut-II / 2011 covering an area of 10,950.92 Ha. Keywords : Forest Area Direction, Protected Forest Area, and Forest Area DevelopmentThis study aims (1) to determine protected forest areas based on scoring analysis in North Konawe District, (2) to determine the direction of protection forest designation in North Konawe District, (3) evaluate the suitability of protected forest areas that have been determined through a Minister of Forestry Decree and Environment with the condition of the direction of forest area in North Konawe Regency, and (4) evaluating the suitability of protected forest areas stipulated in the North Konawe Regency spatial planning document (RTRW) with maps of forest area development. The method or technique of sampling is determined intentionally (purposive sampling), based on field conditions through a Ground Check Ground study to determine field conditions. The sample in this study consisted of forest area managers, community groups, and protected forest areas located in Asera District and LasoloKepulauan District. This research uses descriptive analysis and map overlay analysis. The results showed that (1) The entire administrative area of North Konawe Regency, the area classified as protected forest area based on the scoring criteria was 152,627.00 Ha or 34.52% of the area of North Konawe Regency; (2) The direction of the protected forest area in North Konawe Regency is 147,996.36 Ha which includes Langgikima, Molawe, Oheo, Wiwirano, Motui, Sawa, Lembo, Lasolo, Andowia, Lasolo Islands, and Asera Districts; (3) The suitability of protected forest areas that have been determined through the Decree of the Minister of Forestry and the Environment with the condition of the direction of the forest area in North Konawe Regency is that there is a protected forest area (based on a map of the direction of the forest area) allocated (in the map of forest area development) into a cultivation area (HP) covering an area of 3,493.46 Ha, there are Other Use Areas (APL) in protected forest maps of forest area development covering 10.31 Ha, and there are protected forest areas (in forest area development maps) allocated (based on forest area landing maps) become a cultivation area (HPT) covering an area of 8,051.78 hectares spread throughout the sub-district, so that a limited production forest area of 8,051.78 hectares; and (4) Based on the suitability of the protected forest area stipulated in the North Konawe Regency Spatial Plan (RTRW) with a map of the forest area development there is a difference in the area of the forest area because the North Konawe Regency spatial pattern still uses SK. 465 / Menhut-II / 2011 covering an area of 10,950.92 Ha. Keywords : Forest Area Direction, Protected Forest Area, and Forest Area Development  123